Assessing the Socioeconomic Impact of Gas Extraction Operations on Local Livelihoods in Tanzania - Musoma, Beston Musa; Nyanda, Suzana Samson; Muhanga, Mikidadi Idd; Massawe, Fatihiya Ally (Business, Management and Economics: Research Progress Vol. 4, 2024)
This study underscores the importance of community involvement in decision-making processes regarding gas extraction operations and the equitable distribution of benefits among stakeholders. Communities in rural Tanzania that depend on farming and fishing for their livelihoods are particularly vulnerable to extractive investment ventures. Diversifying a community's sources of income beyond farming and fishing can help it effectively manage the negative effects of extractive investment operations. The lives of communities are predicted to alter and diversify because of gas extraction operations (GEOs). Tanzania has new GEOs; thus, it is necessary to investigate how they have diversified their livelihoods in the Mtwara Rural District. This study addresses the association between GEOs and diversifying livelihoods. This study explores (i) livelihood diversification before and during GEOs, (ii) the associations between GEOs and villagers’ livelihood diversification, and (iii) communities’ perspectives on GEOs and livelihood diversification. Proportionate stratified sampling was used to obtain 260 participants. A questionnaire-based survey, four (4) Focus Group Discussions (FGDs), and fifteen (15) Key Informant Interviews (KIIs) were used to collect the data. IBM-SPSS version 25 was used to analyse quantitative data. The Chi-square test was employed to analyse livelihood diversification in relation to GEOs. Content analysis was used for the qualitative data. Near and distant communities saw a farming decline of 81.5% and 83.5%, respectively. Additionally, fishing declined by 85.2% and 83.7%, respectively. On the other hand, GEOs enhanced motorbike transport by 160.0% and 300.0%, food vending by 166.7% and 236.4%, and seashell collection by 816.0% and 462.5%, respectively. GEOs diversified farming (p = 0.001), fishing (p = 0.008), agricultural labour wages (p = 0.000), and crop business (p = 0.036) with moderate strength of association. In Mtwara Rural District of Tanzania, the study explored that the availability of gas did not encourage the development of manufacturing and processing firms in the research area, forcing neighbourhood households to diversify their income sources. The GEOs have diversified livelihoods in the study area. This study demonstrates that communities surrounding GEOs are highly socioeconomically vulnerable due to GEOs, which caused declining agricultural and fish catches, thus negatively affecting their livelihoods. To raise wages and improve living conditions, long-term initiatives are advised, including the establishment of varied agro-based businesses for the purpose of creating jobs, training for jobs that generate revenue, and agribusiness and technical training. In order to promote livelihood resilience, public and private entities should jointly launch a focused, context-specific project to diversify household incomes among close and far-flung households.